The role of supply chain integration in the relationship between market orientation and performance in SMEs - Simone Regina Didonet; José Roberto Frega; Ana Maria Toaldo; Guillermo Díaz (International Journal of Business Science & Applied Management (IJBSAM), 2014)
The purpose of this paper is to verify the alignment between market orientation and supply chain integration practices for improving performance in small and medium-sized enterprises (SMEs). A model of the relationships between variables was derived from the literature. Data from 327 SMEs were analysed by confirmatory factorial analysis (CFA) to verify the relationships. The findings show that market orientation indirectly and positively influences performance via supply chain integration. The direct relationship between market orientation (MO) and supply chain integration (SCI) was also confirmed. Likewise, the relationship between market orientation and supply chain integration was found to be strong and positive. The findings suggest that the generation of information in market oriented SMEs favours their sharing information both inter- and intra-organizational. A discussion of these findings, the implications for practice, and proposals for further research are provided.
Keywords: 650; market orientation; supply chain integration; performance; SMEs